Technical expertise analysis and modeling in one hundred freestyle for elite female swimmers - Hellard, P.; Avalos, M.; Caudal, N. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
Recent studies had shown the role of the central "governor" (Noakes 2000) and the importance of specific motor pattern training on performance (Termin 2000). Few studies dealt with performance modelling in order to lead to a better understanding of the kinematics factors which influence performance, and to propose a simulation in advance of the laps time and stroke frequencies corresponding to a predicted performance (Arellano et al. 2001). These researches based on multiple regression analysis failed in this purpose because they didn't integrate several complex aspects of the problem. 1-Several technical expertise clusters correspond to similar performances. 2-The relationships between performances and technical parameters are non-linear. 3-Races represent sequential events, so these different parts are inter-dependant (fast start race dragged slow race end).